Application Of Mirror Theraphy On Mr.F With Stroke In The Abimanyu Room At K.R.M.T Wongso Negoro Regional Hospital Semarang - Arba' Putra, Fitkie; Amrih Widiati (Jurnal EduHealth, 2024)
Neurological disorders that can be identified from lost motor function, sudden loss of visual or speech abilities, and caused by blockages formed in the blood vessels of the brain or peripheral organs caused by atherosclerosis are the meaning of non-hemorrhagic stroke. Some things that can be experienced include sudden headaches, feeling dizzy combined with nausea and vomiting, feeling confused, unclear vision, suddenly having difficulty speaking, disturbed balance, feeling numb on one side of the body or tingling. Purpose: describes nursing care by applying mirror therapy to Mr.S with non-hemorrhagic stroke. Methods: Descriptive case studies are used as the following type of research, with the subject Mr. S, 57 years old, male. Data was collected by conducting interviews, physical examinations and observations, as well as collecting data based on documentation studies. Results: Based on studies analyzed during the delivery of mirror therapy intervention with a diagnosis of physical mobility disorders, there was a significant increase in muscle strength during the 7 days of intervention, namely the first day with a muscle strength value of 1 and the seventh day with a muscle strength value of 3, but there were family problems, motivation which decreased during providing interventions that cause the therapy provided to be less than optimal because the patient's focus is disturbed. Conclusion: the provision of mirror therapy can overcome muscle weakness (hemiparesis) in Mr. S with non-hemorrhagic stroke.